2012
DOI: 10.1371/journal.pone.0032570
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side Is Not Fastidious – Dark Septate Endophytic Fungi of Native and Invasive Plants of Semiarid Sandy Areas

Abstract: Dark septate endophytic (DSE) fungi represent a frequent root-colonizing fungal group common in environments with strong abiotic stress, such as (semi)arid ecosystems. This work aimed to study the DSE fungi colonizing the plants of semiarid sandy grasslands with wood steppe patches on the Great Hungarian Plain. As we may assume that fungi colonizing both invasive and native species are generalists, root associated fungi (RAF) were isolated from eight native and three invasive plant species. The nrDNA sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
183
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(213 citation statements)
references
References 56 publications
10
183
1
3
Order By: Relevance
“…In contrast, Microdochium isolates colonized the accessions extensively, although these conclusions were based on fewer strains. As expected based on our (Mandyam et al 2010) and other (Knapp et al 2012) previous studies, the microscopic observations confirmed that Periconia forms melanized microsclerotia in the host cortex, and that Microdochium invariably produces chlamydospores. This supports the utility of the A. thaliana model for DSE symbioses.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, Microdochium isolates colonized the accessions extensively, although these conclusions were based on fewer strains. As expected based on our (Mandyam et al 2010) and other (Knapp et al 2012) previous studies, the microscopic observations confirmed that Periconia forms melanized microsclerotia in the host cortex, and that Microdochium invariably produces chlamydospores. This supports the utility of the A. thaliana model for DSE symbioses.…”
Section: Discussionsupporting
confidence: 91%
“…Although many DSE fungi form similar morphological structures in the host roots (Jumpponen & Trappe 1998, Rodriguez et al 2009), they are taxonomically unrelated, vary in ecological or physiological functions and lead to variable host responses (Addy, Piercey & Currah 2005, Alberton, Kuyper & Summerbell 2010, Newsham 2011, Tellenbach, Grünig & Sieber 2011, Knapp, Pintye & Kovacs 2012. Our earlier studies in the tallgrass prairie concluded that while grasses overall tend to be colonized to a greater extent and respond more positively to DSE colonization, forbs also range from increased to no response to decreased biomass accumulation in their response to DSE fungi (Mandyam, Fox & Jumpponen 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern reflects the general fungal abundance in soils under study as revealed by PLFA analysis (Stefanowicz et al 2016). Knapp et al (2012) found that the same dark septate endophyte isolates were detected from the roots of both alien and native plants in Hungary, supporting the hypothesis that this group of fungi has a wide host range. However, their effect on alien plants and potential role in their invasions remain to be investigated.…”
Section: Discussionsupporting
confidence: 60%
“…El término endófi to se utiliza para defi nir aquel microorganismo que habita dentro del tejido vegetal sin causar ningún daño aparente Knapp et al, 2012); este es el caso de los DSE que han sido encontrados dentro de raíces de diversas especies vegetales pertenecientes tanto a gimnospermas como a angiospermas . Algunos DSE se han identifi cado como los anamorfos de hongos ascomicetos, que en dicho estado producen conidios o son estériles y colonizan las raíces vivas de algunas plantas sin causarles un daño aparente o un desorden tisular Jumpponen, 2001).…”
Section: Identidad Taxonómica Y Aislamientounclassified